Keywords for American cultural studies - Burgett, Bruce 1963-; Hendler, Glenn 1962- (New York University Press, 2014)
Since its initial publication, scholars and students alike have turned to Keywords for American Cultural Studies as an invaluable resource for understanding key terms and debates in the fields of American studies and cultural studies. As scholarship has continued to evolve, this revised and expanded second edition offers indispensable meditations on new and developing concepts used in American studies, cultural studies, and beyond. It is equally useful for college students who are trying to understand what their teachers are talking about, for general readers who want to know what's new in scholarly research, and for professors who just want to keep up. Designed as a print-digital hybrid publication, Keywords collects more than 90 essays--30 of which are new to this edition--from interdisciplinary scholars, each on a single term such as "America," "culture," "law," and "religion." Alongside "community," "prison," "queer," "region," and many others, these words are the nodal points in many of today's most dynamic and vexed discussions of political and social life, both inside and outside of the academy. The Keywords website, which features 33 essays, provides pedagogical tools that engage the entirety of the book, both in print and online. The publication brings together essays by scholars working in literary studies and political economy, cultural anthropology and ethnic studies, African American history and performance studies, gender studies and political theory. Some entries are explicitly argumentative; others are more descriptive. All are clear, challenging, and critically engaged. As a whole, Keywords for American Cultural Studies provides an accessible A to Z survey of prevailing academic buzzwords and a flexible tool for carving out new areas of inquiry. "--